2018
DOI: 10.3389/fgene.2018.00509
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening and Molecular Profile of Congenital Hypothyroidism in a Chinese Population

Abstract: To review the characteristics of newborn screening of congenital hypothyroidism (CH), we reviewed the newborn screening data, including the levels of blood spot thyroid-stimulating hormone (TSH), and serum TSH and free thyroxine (FT4), of all newborn infants who accepted the newborn screening program during the last 14 years. In total, 437,342 newborn infants underwent CH screening and 192 infants were diagnosed with CH and the incidence of CH was 1:2278. The positive rate of the initial screening was 0.96%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 39 publications
2
23
2
Order By: Relevance
“…This was attributed to the fact that the majority of patients were from rural areas and probably have some difficulties in accessing their results of screening as well as in admission to our tertiary pediatric endocrine centre. While in some studies, a female predominance has been reported, some others, showed a male predominance ( 8 , 9 , 10 , 11 , 12 , 13 , 14 ). In the present study, there was a slight female predominance.…”
Section: Discussionmentioning
confidence: 93%
“…This was attributed to the fact that the majority of patients were from rural areas and probably have some difficulties in accessing their results of screening as well as in admission to our tertiary pediatric endocrine centre. While in some studies, a female predominance has been reported, some others, showed a male predominance ( 8 , 9 , 10 , 11 , 12 , 13 , 14 ). In the present study, there was a slight female predominance.…”
Section: Discussionmentioning
confidence: 93%
“…When looking at the evolution of knowledge in sporadic neonatal hypothyroidism, most of the cases with dysgenesis (aplasia, hypoplasia, and ectopic gland) could not be associated with a specific genetic/metabolic defect—despite the tremendous effort to identify some common metabolic pathway defect in thyroid development. The general concept is that, besides exceptions, sporadic CH with dysgenesis is associated with multifactorial multigenic diversity of genetic or epigenetic [ 28 ] defects with low incidence in the population [ 29 , 30 , 31 ]. By contrast, the present results obtained by the familial aggregation analysis suggest that endemic CH may be in part also of genetic origin—in case of severe iodine deficiency, the data highlighted aggregation at an elevated prevalence in at least two families of the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…16 Despite these challenges, a recent study in China examining 437,342 newborns using TSH screening methods with molecular profile was able to detect several mutations, including DUOX2, TG, and TSHR, involved in CH in the Chinese population. 19 The combination of molecular techniques may help clinicians identify high-risk infants for CH based upon specific molecular profiles associated with different ethnic groups. 19 Furthermore, the incorporation of readily available molecular techniques may provide an additional method for confirming and assessing the course of treatment for premature infants or infants presenting with subclinical hypothyroidism.…”
mentioning
confidence: 99%
“…19 The combination of molecular techniques may help clinicians identify high-risk infants for CH based upon specific molecular profiles associated with different ethnic groups. 19 Furthermore, the incorporation of readily available molecular techniques may provide an additional method for confirming and assessing the course of treatment for premature infants or infants presenting with subclinical hypothyroidism. 19 Overall, further research is required to determine which methods or technologies may provide insight into reducing or eliminating factors to differentiate patients based on ethnicity, gender, and medical history.…”
mentioning
confidence: 99%
See 1 more Smart Citation